AB1191 Vitamin d and cd34+ cells as biomarkers of subclinical atherosclerosis and myocardial dysfunction in inflammatory joint diseases. (12th June 2018) - Rodríguez-Carrio, J.; Lo Gullo, A.; Savarino, F.; Aragona, C.O.; Dattilo, G.; Zito, C.; Suárez, A.; Loddo, S.; Atteritano, M.; Saitta, A.; Mandraffino, G.
Abstract : Background: increased cardiovascular (CV) risk in inflammatory joint diseases (IJD) such as rheumatoid (RA) or psoriatic arthritis (PsA) is linked to an impaired vascular homeostasis. Chronic inflammation and immune dysregulation prompt endothelial damage and impair reparative mechanisms. Among them, circulating CD34 +bone marrow-derived progenitors are known to participate in endothelial turnover and improve myocardial neovascularization and ventricular remodelling, likely delaying CV disease development. Among factors related to CD34 +cells mobilisation, a role for vitamin D has emerged in other scenarios. Whether impaired CD34 +cells or vitamin D levels underlie endothelial and myocardial dysfunction in IJD patients remains unknown. Objectives: to evaluate the associations between CD34 +cells and vitamin D levels with markers of subclinical atherosclerosis and myocardial functionality in IJD patients. Methods: CD34 +cells counts were assessed by flow cytometry in peripheral blood samples from 41 RA (2010 EULAR/ACR criteria) and 35 PsA (CASPAR criteria) patients recruited at onset and 58 matched healthy controls (HC). Vitamin D levels were quantified in serum by HPLC. PWV and cIMT were evaluated as markers of subclinical atherosclerosis, whereas myocardial dysfunction was assessed by speckle-tracking echocardiography (STE). Results: vitamin D was decreased in RA (23.68±6.42) and PsA (23.53±4.84) compared to HC (31.75±5.05 ng/ml, both p<0.001). Vitamin D was negatively associated with cIMT in HC (r=−0.308, p=0.026) and in PsA patients with low disease activity (DAS28 <2.9, n=11) (r=−0.636, p=0.035), but not in their high disease activity or RA counterparts. CD34 +cells were decreased in RA compared to HC (1.58±0.58 vs 2.35±1.14 cells/ul, p=0.002). CD34 +cells frequency was associated with total- and LDL-cholesterol levels in HC (r=−0.295, p=0.031 and r=−0.354, p=0.011, respectively) but not in IJD. CD34 +cells negatively paralleled DAS28 in PsA (r=−0.338, p=0.047) and RA (r=−0.303, p=0.057). Multivariate regression analyses revealed that vitamin D levels (B=0.019, p=0.009) and DAS28 (B=−0.152, p=0.050) were independently associated with CD34 +counts in PsA, whereas vitamin D (B=0.010, p=0.028) and duration of the symptoms (B=0.016, p=0.010) did in RA. CD34 +cells counts were correlated with GCS (r=−0.291, p=0.068) and GLS (r=−0.301, p=0.057) in RA. Conclusions: vitamin D was negatively associated with cIMT and risk factors in HC and PsA patients with low disease activity, but not in those with active disease or RA. Vitamin D was an independent predictor of CD34 +cell depletion in IJD. CD34 +cells, negatively associated with risk factors in HC, were altered in RA in relation to disease activity and the duration of symptoms. CD34 +cells were associated with myocardial dysfunction in RA. Disclosure of Interest: None declared